Hipertensão arterial e fatores associados em população remanescente de quilombo de Mata Cavalo - Mato Grosso - Santos, Ediálida Costa (2013)
The prevalence of hypertension is higher in populations afro- descendants, compared to other ethnic groups. In Brazil there is a limited number of publications about this disease in populations of race/color black, in rural areas, in specific groups such as those “quilombos” in west-central, and no study in Mato Grosso. OBJECTIVE- Examine the prevalence of hypertension and associated factors in the population of remnants of the “Quilombo de Mata Cavalo”, rural area of the municipality of Nossa Senhora do Livramento, Mato Grosso, Brasil. METHODS- It is a cross-sectional study, conducted in 2012, with all adults ≥ 18 years residing in the community and attached to the program of Family Health Strategy, which covers the whole area. Through standardized and validated questionnaire, were collected demographic and socioeconomic data, anthropometric and habits of life. Blood pressure was measured three times, using automatic sphygmomanometer OMRON 705-CP. It was considered hypertensive individuals with blood pressure levels ≥140x90 mmHg, or use of antihypertensive medication. The associations between hypertension and the explanatory variables were performed by means of analysis of Poisson regression, with estimates of prevalence ratio and their confidence intervals of 95%. RESULTS- Were studied 261 individuals (81,5% of the eligible population) with the following characteristics: mean age of 51,8 ( ±17,7 ) years, 49% of the female gender, predominance of race/color black and mulatto, low rates of income and education. The overall prevalence of hypertension was 52,5%, with a slight predominance, not significant among women (57% vs 48,1% ). After controlling for confounding factors and adjust by sex and race/color, the variables associated with hypertension were age and family history of the disease. In the studied population, 67,9% knew to be hypertensive, 62% dealt with the disease and only 48,2% had blood pressure controlled. CONCLUSION - The arterial hypertension was independently associated with increased age, and family history. The results point to the importance of new studies, not only in rural communities or of “quilombolas” communities, but especially a nationwide study to obtain epidemiological information more accurate measurements of specific populations, and evaluate the impact of race/ethnic groups and of miscegenation on hypertension in Brazil.